Decisions at Perryville : the twenty-two critical decisions that defined the battle - Peterson, Larry; Kissel, Tim (Knoxville : The University of Tennessee Press, 2022)
"The Battle of Perryville was the culmination of the Confederate Heartland Offensive as General Braxton Bragg's army won a strategic victory over Major General Don Carlos Buell's corps from the Union Army of the Ohio. However, as Bragg retreated into Tennessee shortly after the battle, he effectively granted control of Kentucky to the Union, and the North would hold this critical border state for the remainder of the American Civil War. In Decisions at Perryville, Larry Peterson examines the critical decisions that shaped the way the battle unfolded. Rather than offering a history of the battle, Peterson focuses on the critical decisions confronting Federal and Confederate leaders and ultimately shaping the battle as we know it today"--
The Confederate High Tide: June-December 1862 -- Before the Battle: September 29-October 7, 1862 -- Initiating the Battle of Perryville: October 8, 1862 -- The Battle of Perryville: October 8, 1862 -- After the Battle: October 8-24, 1862 -- Aftermath and Conclusions.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Perryville, Battle of, Perryville, Ky., 1862.; Command of troops -- Case studies; Kentucky -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Campaigns; Bataille de Perryville, Perryville, Kent., 1862.; Commandement des troupes -- Études de cas; Kentucky -- Histoire -- 1861-1865 (Guerre de Sécession) -- Campagnes et batailles; États-Unis -- Histoire -- 1861-1865 (Guerre de Sécession) -- Campagnes et batailles; HISTORY / United States / Civil War Period (1850-1877); Command of troops; Military campaigns; Kentucky; Kentucky -- Perryville; United States; 1861-1865; Case studies; History